Teknologi Pembelajaran: Kesiapan Pemanfaatan Teknologi dan Keterikatan Kerja pada Dosen Generasi X dan Y - Amalia, Rahmatika Sari (Balai Diklat Keagamaan Surabaya, 2024)
Technology is believed to be able to improve in the quality of education, including in Islamic higher education. This has resulted transformation to technology-based education. The readiness of lecturers in facing the transformation to technology-based education determines the success of lecturers in the context of the use of current educational technology. Readiness to face this change in education is predicted to be influenced by how lecturers feel attached to their work. This study aims to determine the effect of work engagement on readiness for change in lecturers at PT. AAA in utilizing educational technology, as well as to determine generational differences in influencing work engagement and readiness for change in lecturers at PT. AAA. This study is a quantitative study using a readiness to change and work engagement measurement scale. The population in this study were lecturers at AAA universities, with a sample size of 171 respondents. The analysis used in this study is regression analysis which aims to determine the effect of work engagement on readiness for change. Meanwhile, the independent sample t-test analysis was used to measure the difference in readiness for change in generations X and Y, while the Mann Whitney test was used to measure the difference in work engagement in generations X and Y. The results of this study indicate that there is a significant influence between work engagement and readiness for change in lecturers in utilizing educational technology at AAA universities. Meanwhile, based on the results of the difference test, it was stated that there was no significant difference in readiness for change between generation X and Y lecturers, whereas in the work engagement variable, a difference was found, but the difference value was not too large.